A descriptive study to assess the maternal and fetal outcome among women with preeclampsia at selected tertiary care hospital, bangalore.karnataka. - C.SANGEETHA; DR.PRASANNA BABY; DR. BALAKRISHNA NAIK (International Journal of Pharma and Bio Sciences, 2018)
Preeclampsia is a specific heterogeneous multisystem disorder. It mainly affects maternal health after pregnancy. It is a considerable public health threat particularly in developing countries. Pre-eclampsia is a condition which typically occurs after 20 weeks of gestation is characterized by high blood pressure which in fact is one of the main contributing factor. Mostly pregnant women identified with preeclampsia have healthy babies, if not treated the pregnancy outcome demonstrates untoward consequences. The study aims to determine maternal and foetal outcome among women with preeclampsia and to associate preeclampsia with selected baseline variable. A descriptive design was used to conduct a study at Selected Tertiary Care Hospital in Bangalore. All antenatal women diagnosed with preeclampsia during May 2015 to December 2016 were assessed to investigated effect of preeclampsia on mother and fetus. Results showed that majority of participants in the study belonged to age group of 26-30 years. Among them, 50% were Primigravida and 40% had previous history of preeclampsia. Among common maternal outcome, 12(19.4%) had antepartum eclampsia and 5(8.1%) had antepartum haemorrhage . With regard to fetal outcome intrauterine deaths and intra uterine growth retardation were seen.. The present study also showed that prematurity and low birth weight are the most common neonatal complications. There was statistically significant association was found between antenatal registration and preeclampsia. Preeclampsia is hypertensive disorders that causes adverse maternal and fetal outcome during pregnancy. The study demonstrates the prevalence of maternal and fetal outcome among women with severe preeclampsia than in mild cases.